KUALITAS PELAYANAN INOVASI PEDULI BAGI PENYANDANG DISABILITAS DI KOTA PEKANBARU - Doni Saputra; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Innovation in local government is essentially a breakthrough aimed at improving and supporting local government performance and providing quality public services. Public services in the field of population administration must be able to reach all levels of society, including people with disabilities. Therefore, there was an innovation from the Pekanbaru City Population and Civil Registration Service called Service for Disabilities to Complete Identity (PEDULI). This program aims to provide maximum service to people with disabilities in Pekanbaru City in obtaining the right to have a resident identity but are constrained by access to transportation to come directly to the Pekanbaru City Disdukcapil office. The purpose of this research is to find out how the quality of the PEDULI Innovation service is for disabilities in Pekanbaru City and to find out what are the inhibiting factors for implementing this innovation. This study used a purposive sampling technique with a qualitative type of research. The necessary data, both primary and secondary data, were obtained by means of interviews and documentation for further analysis using the triangulation method. The results of this study indicate that the program has been running well but still has several obstacles to maximizing its services. The factors that hinder this program are the lack of human resources, inadequate facilities and infrastructure and the lack of support from the community. Suggestions for future improvements are more attention from the local government by improving supporting facilities and infrastructure, collaboration with related agencies, and increasing the competence of human resources to make them more professional. Keywords: Public Service, Disability